2022
DOI: 10.3345/cep.2021.01438
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-guided artificial intelligence technologies for decoding complex multiomics interactions in cells

Abstract: Cells survive and proliferate through complex interactions among diverse molecules across multi-omics layers. Conventional experimental approaches for identifying these interactions have built a firm foundation for molecular biology, but their scalability is gradually becoming inadequate compared to the rapid accumulation of multi-omics data measured by highthroughput technologies. Therefore, the need for data-driven computational modeling of interactions within cells has been highlighted in recent years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…These biologically informed constraints are likely critical to develop successful approaches, as relying on over-parametrized models such as DNN's to learn non-spurious, inspectable relationships is not a reliable strategy (Lee and Kim, 2022 ). However, the strength of over-parametrized models in learning complex relationships cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These biologically informed constraints are likely critical to develop successful approaches, as relying on over-parametrized models such as DNN's to learn non-spurious, inspectable relationships is not a reliable strategy (Lee and Kim, 2022 ). However, the strength of over-parametrized models in learning complex relationships cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…If the generation of these latent factors were instead guided by domain knowledge, resulting groupings may be more likely to hold relevance and rely less on post-hoc analyses for contextualization within the scientific domain. Thus, recognizing the need for greater interpretability of the more opaque integration methods, efforts to combine biological-knowledge-injecting methods such as graph representations or other hard constraints on parameter representations with machine learning methods are ongoing (Noor et al, 2019 ; Lee and Kim, 2022 ), and evaluation and development of mechanisms for handling missing data within these frameworks will be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omics technology is used to study a series of molecules and their interactions involved in the whole process of gene expression from a systems-level, mainly including genomics, transcriptomics, proteomics and metabolomics (Jeong et al2023). With the advances in the technologies and tools for generating and processing large omics data, and the application of arti cial intelligence methodologies for deciphering complex multi-omics interaction, omics technology becomes a powerful approach to decipher the mechanistic details of gene expression (Lee et al 2022). Omics technology is excepted to complement current clinical and pathology evaluations and guide personalized cancer management by discovering previously obscure sub-types with clinical implications and identifying patients' prognoses, which help in revealing the molecular mechanisms and heterogeneity of OS, thereby improving the prognosis of patients (Pan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During the review process, it was identified that CEP published a paper outside its scope. 2) This review article introduced a model of deep learning at the cellular level and provided information on the concept of multiomics, an expanding research area. Topics are not limited to pediatric health or diseases but include generalized research applicable to all basic medical fields.…”
mentioning
confidence: 99%